Maternal Nutritional Empowerment Through “Isi Piringku” Education: Longitudinal Analysis Of Stunting Prevention and Life-Cycle Nutritiona Outcomes (2018-2022 Cohort Study) - Basit, Abdul; Arisanty, Deasy (Journal of Scientific Insights, 2025)
This study aimed to develop and evaluate an empowerment model for pregnant women using "Isi Piringku" ("My Plate") nutrition education to prevent stunting and improve nutritional outcomes. A longitudinal study involving 2,053 pregnant women in South Kalimantan demonstrated that the "Isi Piringku" intervention positively improved maternal nutritional status and reduced childhood stunting prevalence. Key findings included: 99.27% of participants completed ≥4 antenatal care (ANC) visits, 99.22% delivered at healthcare facilities, and 88.11% adhered to iron-folic acid supplementation. Exclusive breastfeeding at six months was reported in 75.06% of cases. Stunting prevalence in Banjarmasin remained below national targets (8.44% in 2019; 9.55% in 2022). The "Isi Piringku" model proved effective for stunting prevention, offering a framework for designing nutritional interventions and raising awareness among pregnant women and communities. Further research is needed to assess the model’s applicability across diverse regions and cultural contexts. These findings may inform stunting prevention programs in other areas.